Kompetensi komunikasi pustakawan di perpustakaan Universitas Islam Negeri Sumatara Utara Medan - Fauzi Eka Putra (UIN Sumatera Utara, 2017)
This article discusses about the competence of librarian communication in the college library. The role of librarians so far helps the user to obtain information by directing the search for information can be efficient, effective, on target, and on time. With the development of information technology, the role of librarians is further improved so that it can serve as a partner for information seekers. The theoretical approach used is core competence, professional, individual and communication competence. Keywords: Competence, communication, Librarian, Library